2017
DOI: 10.1159/000481725
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Trough Concentration of Teicoplanin in Febrile Neutropenic Patients with Hematological Malignancy

Abstract: Background: Teicoplanin is a glycopeptide antibiotic currently used for the treatment of methicillin-resistant Staphylococcus aureus. The need for therapeutic drug monitoring of teicoplanin has been increasingly highlighted as important. It is generally accepted that whereas a plasma trough concentration (Cmin) of ≥10 mg/L is appropriate for the majority of infections, it should exceed 20 mg/L for severe infections. The target Cmin of teicoplanin in patients with febrile neutropenia (FN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Third, the initial dose of teicoplanin was determined so as to attain a target trough concentration of 10‐30 μg/mL. However, for febrile neutropenic patients with bacteremia, the teicoplanin target C min is reported to at least ≥15.2 μg/mL or 15‐20 μg/mL . Many studies have suggested that the standard regimen for teicoplanin does not meet the desired C min for haematological malignancy patients with febrile neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the initial dose of teicoplanin was determined so as to attain a target trough concentration of 10‐30 μg/mL. However, for febrile neutropenic patients with bacteremia, the teicoplanin target C min is reported to at least ≥15.2 μg/mL or 15‐20 μg/mL . Many studies have suggested that the standard regimen for teicoplanin does not meet the desired C min for haematological malignancy patients with febrile neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism of increased clearance due to FN is thought to be augmented renal clearance due to inflammation [14]. To solve this problem, studies have been conducted on the pharmacokinetic parameters specific to patients with cancer [10] and on the optimization of TEIC dosing and blood concentration in patients with hematologic malignancies who develop FN [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Teicoplanin and vancomycin are glycopeptide antibacterials that inhibit bacterial cell-wall peptidoglycan synthesis and are the first-line treatment for drug-resistant Gram-positive bacteria [1]. Both of them are effective in febrile neutropenic patients [7], and compared with vancomycin, teicoplanin has advantages of comparable antibacterial activity, post-antibiotic effect and lower frequency of nephrotoxicity or red-man syndrome [8,9], and so teicoplanin can be used as an initial empirical choice for febrile neutropenic patients with haematological malignancies [10]. Ziglam et al [11] showed that teicoplanin was chosen approximately twice as often as vancomycin for the second-line antimicrobials when empirical therapy did not respond after 24-48 hr for febrile neutropenic patients in oncology units.…”
mentioning
confidence: 99%
“…Maintaining the C min of teicoplanin above 10 mg/L can effectively control general infections . For febrile neutropenic patients with bacteraemia, the teicoplanin C min must be at least ≥15.2 mg/L or 15–20 mg/L . For endocarditis, septicaemia and bone or joint infections, the C min of teicoplanin should exceed 20 mg/L in immunosuppressed patient .…”
mentioning
confidence: 99%
See 1 more Smart Citation